(untitled) - Agency for Instructional Technology and South-Western Educational Publishing; Agency for Instructional Technology,South-Western Educational Publishing (Cincinnati, Ohio)
First impressions, Reading nonverbal messages, Know your customers, Know your company...
Keywords: Customer services; Customer relations; Business communication